Profile of a competent public manager - Mohamed, Ahmad Martadha (Penerbit Universiti Utara Malaysia, 2005)
Much has been said about the public service lately. Most of the time, the opinions tend to be negative. Wasteful, inefficient, arrogant, irresponsive, impersonal,autocratic, and undemocratic are among the harshest criticisms thrown at bureaucracy. Yet, despite these criticisms, public service plays essential roles in implementing and enforcing government policies. Many people whose lives have been affected by government agencies though a variety of policies in areas such as income redistribution, environmental protection, crime prevention, and healthcare management realize the importance of those agencies. The proliferation of these bureaucratic activities further expands the functions of traditional bureaucracies and transforms them into formidable forces. One of the major reasons for the expansion of bureaucracy is industrialization. As a result, the growth of bureaucracy during the twentieth century had been phenomenal. In the United States, there were about 2.8 million civil servants in 1980 compared to only about 240,000 at the turn of the century (Krislov and Rosenbloom, 1981). In Malaysia, the total number of personnel in the public service on January, 1999 was 664,166 (excluding the Police and the Armed Forces) (Ahmad Atory, 2001).